2001
DOI: 10.1002/1521-3773(20010202)40:3<469::aid-anie469>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture

Abstract: The cover picture shows schematically the conditions for preparation and decomposition of strontium diazenides. The crystal structures of the diazenides, which were obtained as single‐phase products under high N2 pressure (up to 5500 bar), were determined by neutron diffraction. The background is provided by a section of the powder diffraction pattern of SrN2, and the coordination of the diazenide ions is shown top right. The N−N bond length in the diazenide ions is 122 pm in both compounds. Details of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…The Rietveld analysis revealed that the nitrogen dimer distance of marcasite-type NiN 2 at 36.0 GPa is 1.24 Å while it might involve a large uncertainty because of low scattering factor of nitrogen. However, the nitrogen dimer distance of nickel pernitride would be comparable to that of FeN 2 , [14,15] CuN 2 , [16] BaN 2 , [28] and SrN 2 , [29] and the relation between bulk modulus and nitrogen dimer distance inferred from the previous studies is applicable for the nickel pernitride. On the other hand, the bulk modulus might be attributed to not only the state of N-N dimer but also the other factors.…”
Section: Resultsmentioning
confidence: 87%
“…The Rietveld analysis revealed that the nitrogen dimer distance of marcasite-type NiN 2 at 36.0 GPa is 1.24 Å while it might involve a large uncertainty because of low scattering factor of nitrogen. However, the nitrogen dimer distance of nickel pernitride would be comparable to that of FeN 2 , [14,15] CuN 2 , [16] BaN 2 , [28] and SrN 2 , [29] and the relation between bulk modulus and nitrogen dimer distance inferred from the previous studies is applicable for the nickel pernitride. On the other hand, the bulk modulus might be attributed to not only the state of N-N dimer but also the other factors.…”
Section: Resultsmentioning
confidence: 87%
“…These measurements are in good agreement with the reported value for SrN 2 of 320°C upon heating SrN 2 in vacuum. 10,14 It is noteworthy that all three alkaline earth diazenides react analogously forming the respective subnitrides M AE 2 N upon heating. In the case of strontium and barium diazenide this behavior seems reasonable as the stoichiometric nitrides M AE 3 N 2 do not seem to exist.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Details of the setup are described in the literature. 34−38 CaN 2 (SrN 2 , BaN 2 ) was synthesized in a 14/8 (18/11, 18/11) assembly which was compressed up to 12 (9, 3) GPa at room temperature within 325 (214, 68) minutes, then heated up to 800 (550, 450)°C in 300 (30,30) minutes, kept at this temperature for 20 (15,15) minutes and cooled down to room temperature in 15 (10,10) minutes. Subsequently, the pressure was released over a period of 958 (623, 183) minutes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sincethepioneeringresearchintobinarynitrides, [1] this field of chemistry has grown into arich diversity of sub-classes. [2][3][4][5][6][7][8][9] One of the families that has been investigated more intensely is that of iron nitrides.S everal different phases are already known, [10] which range from the most iron-rich phases,such as a''-Fe 16 N 2 or a'-Fe 8 Nthrough g'-Fe 4 N, e-Fe 3 N 1AEx and z-Fe 2 Nto g'''-FeN, [11] which represents the most nitrogen-rich phase to date.However,in2011, the existence of nitrogen-richer FeN 2 was predicted. [12] Iron nitrides are used as coatings for steelbased materials combining hardening with protection against corrosion.…”
mentioning
confidence: 99%